The Predictive Brain Must Have a Limitation in Short-Term Memory Capacity. (October 2021) - Trapp, Sabrina; Parr, Thomas; Friston, Karl; Schröger, Erich
Traditionally, short-term memory (STM) has been assessed by asking participants to remember words, visual objects, or numbers for a short amount of time before their recall or recognition of those items is tested. However, this focus on memory for past sensory input might have obscured potential theoretical insights into the function of this cognitive faculty. Here, we suggest that STM may have an important role in predicting future sensory input. This reconceptualization of STM may provide a functional explanation for its capacity limitation.